2006
DOI: 10.1002/pola.21869
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of optically active poly(N‐propargylsulfamides) with helical conformation

Abstract: A novel chiral N‐propargylsulfamide monomer (1a) and its enantiomer (1b) were synthesized and polymerized with (nbd)Rh+B−(C6H5)4 as a catalyst providing poly(1) (poly(1a) and poly(1b)) in high yields (≥99%). Poly(1) could take stable helices in less polar solvents (chloroform and THF), demonstrated by strong circular dichroism signals and UV–vis absorption peaks at about 415 nm and the large specific rotations; but in more polar solvents including DMF and DMSO, poly(1) failed to form helix. Quantitative evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
70
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 52 publications
9
70
0
Order By: Relevance
“…The results with respect to UV-Vis absorption spectra are similar to some mono-substituted polyacetylenes studied by us earlier, e.g., poly(N -propargylsulfamide)s [34] and poly(N -propargylurea)s [26]. However, under the investigated conditions, the present poly(N -propargylthiourea)s failed to form helical conformations, which were frequently observed in mono-substituted polyacetylenes [23][24][25]35]. The lacking of ordered helical conformations in the currently studied poly(N -propargylthiourea)s is assumed to be originated in the two -N-H groups of poly(4) in the pendant chains.…”
Section: Uv-vis Spectrum Of M4 and Poly(4)supporting
confidence: 56%
See 2 more Smart Citations
“…The results with respect to UV-Vis absorption spectra are similar to some mono-substituted polyacetylenes studied by us earlier, e.g., poly(N -propargylsulfamide)s [34] and poly(N -propargylurea)s [26]. However, under the investigated conditions, the present poly(N -propargylthiourea)s failed to form helical conformations, which were frequently observed in mono-substituted polyacetylenes [23][24][25]35]. The lacking of ordered helical conformations in the currently studied poly(N -propargylthiourea)s is assumed to be originated in the two -N-H groups of poly(4) in the pendant chains.…”
Section: Uv-vis Spectrum Of M4 and Poly(4)supporting
confidence: 56%
“…In appearance, poly(4) itself (Fig. 6a) appeared pale yellowish, similar to the other substituted polyacetylenes synthesized in our earlier studies [25,36,37]. The color of the metal complexes gradually became deeper with increasing amounts of Fe 3+ ions.…”
Section: Thermal Stability Of Poly(4)mentioning
confidence: 64%
See 1 more Smart Citation
“…Our previous investigations 16 showed that poly(N-propargylsulfamides), one of the substituted polyacetylenes could take helical conformation. However, the effect of solvent composition on the secondary structure of this new class of helical polymer has not been studied.…”
mentioning
confidence: 99%
“…16 The main procedures are as follows. 1R-(À)-10-camphorsulfonyl chloride (5 g, 20 mmol), pyridine (3.2 mL, 40 mmol) and propargylamine (2.8 mL, 40 mmol) were added into diethyl ether (ca.…”
mentioning
confidence: 99%